2014
DOI: 10.1186/1471-244x-14-128
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and burden of subthreshold generalized anxiety disorder: a systematic review

Abstract: BackgroundTo review the prevalence and impact of generalized anxiety disorder (GAD) below the diagnostic threshold and explore its treatment needs in times of scarce healthcare resources.MethodsA systematic literature search was conducted until January 2013 using PUBMED/MEDLINE, PSYCINFO, EMBASE and reference lists to identify epidemiological studies of subthreshold GAD, i.e. GAD symptoms that do not reach the current thresholds of DSM-III-R, DSM-IV or ICD-10. Quality of all included studies was assessed and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
166
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 219 publications
(173 citation statements)
references
References 68 publications
2
166
1
4
Order By: Relevance
“…In this review, older age groups showed the lowest estimates of past‐year subthreshold GAD (3%) (Haller et al. 2014). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this review, older age groups showed the lowest estimates of past‐year subthreshold GAD (3%) (Haller et al. 2014). …”
Section: Resultsmentioning
confidence: 99%
“…2006; Haller et al. 2014). In one review, response rates across studies ranged from 45.9% to 99.5% (Steel et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anxiety is a common and disabling mental health condition [1]. It can greatly impair a person's functioning, quality of life and well-being [2].…”
Section: Introductionmentioning
confidence: 99%